2022
DOI: 10.1111/mec.16500
|View full text |Cite
|
Sign up to set email alerts
|

Complementary genomic and epigenomic adaptation to environmental heterogeneity

Abstract: While adaptation is commonly thought to result from selection on DNA sequencebased variation, recent studies have highlighted an analogous epigenetic component as well. However, the relative roles of these mechanisms in facilitating population persistence under environmental heterogeneity remain unclear. To address the underlying genetic and epigenetic mechanisms and their relationship during environmental adaptation, we screened the genomes and epigenomes of nine global populations of a predominately sessile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…These molecular and epigenetic regulations may contribute to the emergence of new adaptive traits and genotypes in new habitats (Drenovsky et al, 2012; Green et al, 2020). As compared to terrestrial systems (Mounger et al, 2021; Xu et al, 2019), understanding these patterns in marine systems has not been explored to the same extent (Gao et al, 2022; Huang, Li, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These molecular and epigenetic regulations may contribute to the emergence of new adaptive traits and genotypes in new habitats (Drenovsky et al, 2012; Green et al, 2020). As compared to terrestrial systems (Mounger et al, 2021; Xu et al, 2019), understanding these patterns in marine systems has not been explored to the same extent (Gao et al, 2022; Huang, Li, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Significant associations between genetic or epigenetic variation and environmental parameters (e.g. temperature or salinity) have previously been reported in various invertebrates [24][25][26][27][28] , with significant correlation between genetic and epigenetic variation found in six of 14 studies reviewed 29 . Analyses of genetic control of epigenetic variation using methQTL have found that the fraction of epigenetic variation under direct control of DNA sequence variation 25,27,30 is highly variable, ranging from 2% in the threespine stickleback (Gasterosteus aculeatus) 30 , 3% in the Olympia oyster (Ostrea lurida) 27 , 19% in Ciona intestinalis 25 , 70% in human (Homo sapiens) 31,32 , and 88% in this study.…”
Section: Discussionmentioning
confidence: 92%
“…Significant associations between genetic or epigenetic variation and environmental parameters (e.g., temperature or salinity) have previously been reported in various invertebrates (25)(26)(27)(28)(29), with a significant correlation between genetic and epigenetic variation found in 6 of 14 studies reviewed (30). MethQTL mapping revealed that the fraction of epigenetic variation associated with DNA sequence variation (26,28,31) is highly variable, ranging from 2% in the threespine stickleback (Gasterosteus aculeatus) (31), 3% in the Olympia oyster (Ostrea lurida) (28), 19% in Ciona intestinalis (26), 70% in human (Homo sapiens) (32,33), and 88% in this study.…”
Section: Discussionmentioning
confidence: 93%